Effects of Oryzanol and Tocotrienol on Platelet Aggregation and Blood Lipid Profile in Rats - Maliki, Nur Zillah (2007)
Rice bran is the outer brown layer of the rice kernel that is removed during the milling process to produce white rice. The bran portion of the rice kernel is one of the most nutritious portions of the kernel. Recently, there are evidences suggesting that key components of rice may play a role in health maintenance and disease prevention. Fully-processed rice bran oil contains higher amount of unsaponifiable components than most vegetable oils. The focus has been on oryzanol and vitamin E, especially tocotrienols which were found to have many health benefits. Thus, this project was undertaken to determine the effect of oryzanol in combination with tocotrienol on platelet aggregation, plasma lipid profile, kidney and liver function parameters and the histology of the aorta in rats. A total of 140 male Sprague-Dawley rats with body weights ranging from 230 to 280 g were divided into 2 treatment batches (n=70/batch). The first batch received intervention treatment while receiving a high cholesterol diet. The second batch was given a high cholesterol diet for one month before treatment and followed by normal rat chow at the time the dietary treatment was instituted. In the first treatment batch, a total of 70 rats were randomly distributed into 7 groups (n=10/group); Control, HCD (Control + 1% cholesterol + 0.15% cholic acid), HCD + ASA (HCD + 0.5% aspirin), HCD + ORY (HCD + 0.5% oryzanol in triolein), HCD + TRF (HCD + 0.5% tocotrienol-rich fraction in triolein), HCD + OT (HCD + 0.5% oryzanol + tocotrienol in triolein) and HCD + EMUL (HCD + 0.5% oryzanol + tocotrienol emulsion). Each group of animals was fed one type of diet treatment only and allowed free access to water throughout the study period. Treatments were applied by oral gavage for 8 weeks. Blood samples were collected rice throughout this study; at 0 week, 4 weeks and 8 weeks of treatment. The second treatment batch on the other hand received intervention diets after hypercholesterolemia induction. They were also randomly distributed into 7 groups (n=10/group); Control, HCD (Control + 1% cholesterol + 0.15% cholic acid), ASA (0.5% aspirin), ORY (0.5% oryzanol in triolein), TRF (0.5% tocotrienol-rich fraction in triolein), OT (0.5% oryzanol + tocotrienol in triolein) and EMUL (0.5% oryzanol + tocotrienol emulsion). All groups were fed with high cholesterol diet (normal + 1% cholesterol + 0.15% cholic acid) for 4 weeks except for Control group, which was fed with normal rat chow. The hypercholesterolemic rats were then orally treated for 8 weeks. The blood samples were collected 4 times throughout this experiment; at the beginning of the experiment (pre-induction week), 4 weeks after induction with cholesterol (0 week) and at 4 and 8 weeks of treatment. At the termination of the experiment, the rats were weighed and blood was collected by cardiac puncture. Complete autopsies were performed after the rats had been sacrificed. The rats were dissected and the aortas removed, opened longitudinally, and prepared for detection and estimation of lipid deposits in the intima. The part of the aorta proximal to the heart was cut, labeled, fixed in 10% formalin and prepared for light microscopy examination hematoxylin and eosin (H & E). Whole blood was analysed for platelet aggregation. The total cholesterol (TC), low density lipoprotein (LDL), high density lipoprotein (HDL), and triglyceride (TG), alanine aminotransferase (ALT), γ-glutamyltransferase (GGT), urea, and creatinine plasma concentrations were also analysed. The present study demonstrates that all treatments (ASA, ORY, TRF, OT and EMUL) reduced plasma TC and LDL concentrations and inhibit platelet aggregation in rats. The oryzanol and tocotrienol combination showed the highest inhibition on platelet aggregation in the first treatment batch by –42.33%, -35.94%, and –61.40% and in the second batch by -54.04%, -57.80%, and –69.20% with 10 μl adenosine-5’-diphosphate (ADP), 20 μl ADP, and 20 μl collagen respectively. The results from this study have shown that the combination of oryzanol and tocotrienol is potentially a good hypocholesterolemic agent. In addition, treatment with combination of oryzanol and tocotrienol in triolein showed significant decreases (p<0.05) in plasma TC and LDL concentrations in first batch of rats by –10% and -36% and in the second batch by - 37.5% and –73.49% respectively. Treatment with oryzanol either oryzanol plus tocotrienol in triolein or oryzanol plus tocotrienol emulsion decreased the concentrations of kidney (urea and creatinine) and liver (ALT and GGT) function parameters suggesting that there is no toxic effect on the kidneys or liver. Histological assessment also showed that the blood vessel tissues were not affected by the treatment. No lipid deposit was detected in the aorta of rats. In summary, these studies suggested that in hypercholesterolemic rats the combination of oryzanol and tocotrienol have a synergistic effect. The results indicated that various components of rice bran have potential as anti-platelet aggregation and hypocholesterolemic agents. Therefore, the synergistic properties of oryzanol and tocotrienol could play an important role in reducing the risk of development of cardiovascular disease